Ptyalism gravidarum - Suzuki, Shunji (Medknow Publications & Media Pvt Ltd, 2009)
CONTEXT: Ptyalism gravidarum is of unknown origin and is usually defined as an excessive secretion of saliva, common in women with nausea and vomiting who might have difficulty in swallowing their saliva. CASE REPORT: We present here 2 cases complicated by ptyalism gravidarum during all trimesters of pregnancy. In one case, ptyalism recovered spontaneously at 35-36 weeks’ gestation, and in the other case, it recovered after delivery. CONCLUSION: Ptyalism gravidarum may not be a serious condition leading to adverse perinatal outcomes, however there may not be any satisfactory treatment.